THE STUDENT’S RESPONSES TO THE USE OF COMIC STRIPS AS A LEARNING MEDIA - Zulhasmi Abasa; Zohri Hamdani; Darwanto; Balqis Husain (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
The purpose of this study is to describe the students' responses to the use of comic strips as a learning medium in class VIII MTs N1 Morotai. This research used a quantitative method and included 38 eighth-grade students. This research employs a genuine experimental procedure, using random sampling as the sampling strategy. In the learning process, this instrument is utilized as a questioner following the comic strip treatment. As a result of this study, seven things are right or legitimate, while the other three are incorrect. Valid items ranging from 0.374 to 0.545 with an r-table of 5% were 0.320. Out of the 10 things tested, only seven were correct. The indicator selection revealed that the lowest score was 28 and the highest score was 45. The indicator of learning independence was assigned a score of 37.45, while the final one was assigned a score of 38.32 as an indicator of media presentation. Although comic strip media has limits, many other respondents think that they outweigh these drawbacks. The majority of responders believe it helps pupils enhance their writing skills.